Aging and the interaction between education, retirement and the working life - Omtzigt, D (Department of Economics (University of Oxford), 2006)
Population aging and the burden it imposes on state finances is one of the major economic challenges governments around the world face. Responses are formulated in terms of either increasing employment (for example by raising the retirement age) or increasing productivity (investment in education). This paper brings together these two responses in a unified framework and shows how the individual’s education and retirement decisions are affected by population aging – caused either by a fall in the population growth rate, or an increase in life expectancy - and the budget balancing mechanism of the public pension systems. We discuss how a budget balancing mechanism can be informed by fairness considerations and we show that early retirement can be the result of the application of Musgrave’s rule in response to a fall in fertility.